2012
DOI: 10.1155/2012/473790
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Germ Cell Tumor with Extensive Yolk Sac Tumor Elements in the Frontal Lobe of an Adult

Abstract: Intracranial nongerminomatous germ cell tumors (NGGCTs) in unusual locations are extremely rare. Here, we report a case of a yolk sac tumor in the frontal lobe in a middle-aged patient. A 42-year-old man was admitted to our hospital for headache and nausea. Magnetic resonance imaging (MRI) showed an enhanced mass lesion with a marked cyst component. The serum alpha-fetoprotein (αFP) level was extremely high. Histological examination of specimens after subtotal removal revealed a primary mixed germ cell tumor w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…In most cases, the onset of YST occurs in childhood and young adulthood. In the relevant English literature, there are only 5 reported cases of YST in patients over 35 years old ( Table 1 ) ( 23 - 27 ). Our case represents the fourth-oldest patient with adult-onset yolk sac tumor reported worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, the onset of YST occurs in childhood and young adulthood. In the relevant English literature, there are only 5 reported cases of YST in patients over 35 years old ( Table 1 ) ( 23 - 27 ). Our case represents the fourth-oldest patient with adult-onset yolk sac tumor reported worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…There have been 24 cases of germinoma of the medulla oblongata and the fourth ventricle reported in the literature ( Table 2 ). Eighteen of these cases were reported from East Asian countries (Japan, n=11; Taiwan, n=3; China, n=3; Thailand, n=1) ( 3 - 7 , 9 - 11 , 13 , 15 - 18 , 20 , 23 ). Sixteen of the 24 cases were women, and 2 cases were men with Klinefelter syndrome (chromosomal karyotype: 47, XXY).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were similar to those reported in the literature and suggested a diagnosis of germ cell tumour. Takahashi et al have reported a case of an NGGCT with a frontal lobe lesion [ 6 ]. Often these synchronous lesions with a background of detectable b-HCG and normal to mildly raised AFP are empirically diagnosed as germinomatous germ cell tumours [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the intracranial manifestations, YSTs are typically located midline in the pineal region or the suprasellar region (3). One case of mixed GCT with extensive yolk sac elements outside the midline (in the frontal lobe) in an adult was also reported (16).…”
Section: Discussionmentioning
confidence: 99%